2015
DOI: 10.1111/bph.13193
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of the degeneration of human dopaminergic neurons in an astrocyte co‐culture system allowing endogenous drug metabolism

Abstract: BACKGROUND AND PURPOSEFew neuropharmacological model systems use human neurons. Moreover, available test systems rarely reflect functional roles of co-cultured glial cells. There is no human in vitro counterpart of the widely used 1-methyl-4-phenyl-tetrahydropyridine (MPTP) mouse model of Parkinson's disease EXPERIMENTAL APPROACHWe generated such a model by growing an intricate network of human dopaminergic neurons on a dense layer of astrocytes. In these co-cultures, MPTP was metabolized to 1-methyl-4-phenyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 70 publications
1
60
1
1
Order By: Relevance
“…Quantification of neuronal area was based on selective immunostaining (see below) of neuronal βIIItubulin (Tuj1 antibody) and high-content imaging: An Array-Scan VTI HCS Reader (Cellomics, PA) was used for image acquisition. Thirty fields per well (330 μm × 330 μm size each) were imaged and analyzed (Efremova et al 2015). The software recognizes the Tuj-positive pixels and calculates the total pixel number per well.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
See 4 more Smart Citations
“…Quantification of neuronal area was based on selective immunostaining (see below) of neuronal βIIItubulin (Tuj1 antibody) and high-content imaging: An Array-Scan VTI HCS Reader (Cellomics, PA) was used for image acquisition. Thirty fields per well (330 μm × 330 μm size each) were imaged and analyzed (Efremova et al 2015). The software recognizes the Tuj-positive pixels and calculates the total pixel number per well.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…We used here a recently established co-culture model (Efremova et al 2015) of LUHMES neurons and IMA astrocytes. Three-dimensional imaging by confocal microscopy confirmed that neurons are mostly positioned in a layer above the astrocytes, and that both neurites and somata establish large contact interfaces with astrocytes ( Fig.…”
Section: Astrocytic Support Of Neurons and Attenuation Of Neurotoxicitymentioning
confidence: 99%
See 3 more Smart Citations